2020
DOI: 10.1109/lpt.2019.2960112
|View full text |Cite
|
Sign up to set email alerts
|

2.4 GHz L-Band Passively Harmonic Mode Locked Er-Doped Fiber Laser Based on Carbon Nanotubes Film

Abstract: We experimentally demonstrate a passively harmonic mode locked (PHML) Er-doped fiber laser with pump power efficiency up to 17 MHz/mW operating at L-band based on single walled carbon nanotubes polyvinyl alcohol (SWCNTs-PVA) film. Under 233 mW pump power, the stable pulse train at 1594.97 nm with 40.5 dB side mode suppression ratio (SMSR) and 742 fs pulse duration is obtained at a repetition rate of 1.923 GHz, corresponding to 170 th harmonic of the fundamental frequency. Under optimized intracavity conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Various operation regimes, including Q-switching [52,53,[66][67][68][69][70][71], Q-switched mode-locking [72], and mode-locking [9,37,50,[73][74][75][76], were reported. Pulse evolution and interaction dynamics, including various soliton types [9,37,55,[77][78][79], soliton molecule [74,80,81], harmonic mode-locking [58,75,82], vector solitons [83,84], dark soliton [85], and soliton rains [86,87], were observed based on SWCNT-SAs and MWCNT-SAs. Due to the technical advantages of high beam quality, high efficiency, high integration, high reliability, etc., of fiber lasers, in this section, we mainly focus on the CNT-SA-based ultrafast fiber lasers.…”
Section: Cnt-based Ultrafast Fiber Lasermentioning
confidence: 98%
See 2 more Smart Citations
“…Various operation regimes, including Q-switching [52,53,[66][67][68][69][70][71], Q-switched mode-locking [72], and mode-locking [9,37,50,[73][74][75][76], were reported. Pulse evolution and interaction dynamics, including various soliton types [9,37,55,[77][78][79], soliton molecule [74,80,81], harmonic mode-locking [58,75,82], vector solitons [83,84], dark soliton [85], and soliton rains [86,87], were observed based on SWCNT-SAs and MWCNT-SAs. Due to the technical advantages of high beam quality, high efficiency, high integration, high reliability, etc., of fiber lasers, in this section, we mainly focus on the CNT-SA-based ultrafast fiber lasers.…”
Section: Cnt-based Ultrafast Fiber Lasermentioning
confidence: 98%
“…Due to the excellent properties for saturation absorption, CNT-SA has been widely used in Q-switched and modelocked lasers, including the solid-state lasers [45][46][47][48][49], semiconductor lasers [50], waveguide lasers [51], and fiber lasers. The excellent properties of CNT-SAs enable ultrastable, ultrashort, and compact fiber laser system working from the visible to the mid-infrared spectral region [52][53][54][55], with functionalized operations like gigahertz repetition rate [56][57][58], multi-wavelength output [36,59,60], pulse duration, and spectral bandwidth tunability [37,[61][62][63][64][65]. Various operation regimes, including Q-switching [52,53,[66][67][68][69][70][71], Q-switched mode-locking [72], and mode-locking [9,37,50,[73][74][75][76], were reported.…”
Section: Cnt-based Ultrafast Fiber Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…We have carried out a systematic exploration on the effects of average cavity dispersion and spectral bandwidth on HML in L-band using similar laser scheme [203]. It was found that the single pulse energy was eventually determined by the product of the average cavity dispersion and spectral bandwidth (dispersion bandwidth product, DBP) if other parameters such as average nonlinearity parameter, the time bandwidth product and center wavelength were CNT film with lower modulation depth was incorporated [204]. The pulse performances were shown in Figure 5C-E, and the corresponding pulse energy was decreased to 2.41 pJ, which is the lowest pulse energy ever obtained in a PHML fiber laser using a CNT SA, indicating effective cavity management.…”
Section: G-hz Fiber Lasersmentioning
confidence: 99%
“…To achieve a high-repetition rate (HRR) pulse train, a variety of passive mode-locking mechanisms have been reported, such as harmonic mode locking [ 12 , 13 , 14 ], short cavity [ 15 , 16 ], and dissipative four-wave mixing (DFWM) [ 17 , 18 ]. Compared to harmonic mode locking and short cavity, DFWM is a simpler and more effective method to generate an HRR pulse train with a capability even up to terahertz.…”
Section: Introductionmentioning
confidence: 99%